CARP: Range Query-Optimized Indexing for Streaming Data - Jain, Ankush; Cranor, Charles D.; Zheng, Qing; Settlemyer, Bradley W.; Amvrosiadis, George; Grider, Gary A. (SC24: International Conference for High Performance Computing, Networking, Storage and Analysis, 2024)
Ingestion of data generated by high-performance scientific applications continues to stress available storage resources. Efficient range-based analyses on this data can be enabled by reordering it on attributes of interest, but require expensive post-processing sorts to realize the query benefits of reordering. In-situ indexing techniques, while write-efficient, are orders of magnitude slower at range queries than sorted indices. Range queries are necessary for analyzing continuous physical attributes and tracking phenomena such as energy bands and wave fronts. We present CARP, a scalable data partitioner for range queries that reorders data in-situ as it is streamed to storage during application I/O. Motivated by our findings that real application distributions tend to be highly skewed and dynamic, CARP dynamically discovers and adapts its data partitions to track these characteristics. As a result, CARP can approximate the query performance of a sort without any ingestion overhead, making it 5 × faster than prior work.